The Escort System: A Safety Monitor for People Living with Alzheimer's Disease - Taub, Daniel M; Leeb, Steven B; Lupton, Elmer C; Hinman, Roderick T; Zeisel, John; Blackler, Susan (IEEE pervasive computing, 2011)
The Escort system monitors residents of assisted living communities and alerts caregivers when they walk aimlessly, or "wander," into potentially dangerous situations. The system could help lead to improved care at reduced cost.